Implementation of Value Based Breast Cancer Care. Issue 7 (July 2019) - van Egdom, L.S.E.; Lagendijk, M.; van der Kemp, M.H.; van Dam, J.H.; Mureau, M.A.M.; Hazelzet, J.A.; Koppert, L.B.
Abstract: Purpose: Adding value of care to patients is crucial for all stakeholders. The use of both provider and patient reported outcome data was implemented in a single academic breast cancer center. We describe the development of the outcomes set, data integration within electronical health records (EHR) and clinical use. Methods: An Integrated Practice Unit (IPU) was constructed providing the full care cycle for breast cancer patients. Provider reported outcomes and patient reported outcomes (PROs) were defined, reflecting the entire cycle of care and long-term sustainability of quality of life. Multidisciplinary provider and patient perspectives were obtained via focus groups and surveys. Patient pathways were redesigned in order to identify suitable opportunities for data collection during the entire care cycle. Results: A Standard Set for Breast Cancer Outcomes together with case-mix variables and timelines was agreed upon within the IPU. A secure electronic platform, directly linked to the EHR, was designed to measure PROs during the outpatient phase. First year evaluation showed a decrease of response rates over time, from 83.3% at baseline to 45.2% at 12 months after surgery. Patients reacted positively to the use of PROMs in daily clinical cancer care. Conclusion: Assessment of patient reported as well as provider reported outcomes was implemented within our standard of breast cancer care. For this, dedicated resources, change of culture and practice, and improved knowledge and awareness about Value-based healthcare (VBHC) were essential. Our proposed framework aims to serve as a blueprint for implementation of VBHC in daily care.